Dozen of doses: A bibliographical journey (Orthodontic Journal of Nepal, 2017)
Orthodontic Journal of Nepal (OJN) completes one dozen issues of publication. OJN is the official publication of Orthodontic and Dentofacial Orthopedic Association of Nepal (ODOAN). The journal was launched on November 15, 2011 during the inaugural ceremony of Joint Scientific Conference of ODOAN and Pierre Fauchard Academy; which was the second conference organized by the association. Since 2013, OJN has been publishing biannually; which was initiated as an annual issue.